Interações entre variáveis bioquímicas sanguíneas no período de transição e indicadores de eficiência reprodutiva em vacas leiteiras criadas a pasto - SILVA, Gustavo Feliciano Resende da (2011)
This study was designed to evaluate the changes of some blood biochemical variables during the transition period as an indicative of metabolic diseases and to correlate them with the calving-first estrus interval, calving- conception interval, conception rate per service and parity in dairy crossbred cows raised in pasture based system. Sixty-three cows were evaluated during 12 months. Serum sodium, potassium, calcium (ion selective), glucose, triglycerides and betahyidroyibutyrate (BHB) were measurement in serum samples obtained at different times during the three weeks before and three weeks after calving. No significant differences were observed for the values of sodium, potassium, calcium, glucose and BHB between the pre-and postpartum, but triglyceride concentrations differed (p <0.05), with lower values in the postpartum. Regarding parity, significant differences (p <0.05) between the concentrations of sodium, potassium and calcium were present. For calcium during the prepartum period, lower concentrations were found in animals calving. Interval from calving to first estrus variable (PSPI), differences were observed (p <0.05), with higher calcium concentrations for animals with IPPE up to 45 days and from 45 to 85 days for animals with IPPE above 85 days. For the interval delivery design changes observed for the variable triglycerides (p> 0.05). The data showed that, under the conditions present in this study metabolic changes indicative of metabolic diseases, even subclinical are not present.